Effect of increasing inoculum sizes of pathogenic filamentous fungi on MICs of antifungal agents by broth microdilution method. - Gehrt, A (1995)
Inoculum size is a critical variable in development of methods for antifungal susceptibility testing for filamentous fungi. In order to investigate the influence of different inoculum sizes on MICs of amphotericin B, 5-fluorocytosine, itraconazole, and miconazole, 32 clinical isolates (8 Aspergillus fumigatus, 8 Aspergillus flavus, 5 Rhizopus arrhizus, 8 Pseudallescheria boydii, and 3 Fusarium solani isolates) were studied by the broth microdilution method. Four inoculum sizes were studied: 1 x 10(2) to 5 x 10(2), 1 x 10(3) to 5 x 10(3), 1 x 10(4) to 5 x 10(4), and 1 x 10(5) to 5 x 10(5) CFU/ml. The National Committee for Clinical Laboratory Standards reference method for antifungal susceptibility testing in yeasts was modified and applied to filamentous fungi. The inoculum was spectrophotometrically adjusted, and all tests were performed in buffered medium (RPMI 1640) at pH 7.0 with incubation at 35 degrees C for 72 h. MICs were read at 24, 48, and 72 h. Amphotericin B showed a minimum effect of inoculum size on MICs for all species with the exception of P. boydii (P < 0.05). A significant effect of inoculum size on MICs was observed with 5-fluorocytosine, for which there was an increase of more than 10-fold in MICs against all Aspergillus spp. between inoculum concentrations of 10(2) and 10(4) CFU/ml (P < 0.001). For itraconazole, the results showed a more species-dependent increase of MICs, most strikingly for R. arrhizus and P. boydii. Miconazole, which was tested only with P. boydii, did not demonstrate a significant effect of inoculum size on MICs.(ABSTRACT TRUNCATED AT 250 WORDS)